The politics of poverty - Hadimani, R. N. (New Delhi : Ashish, 1984)
Study of the factors responsible for restricting the efficient implementation of the anti-poverty programs; based on empirical data from a village in Bangalore District, Karnataka.
Includes bibliographical references and index.
Keywords: Rural poor -- India -- Chakrabhavi; Economic assistance, Domestic -- India -- Chakrabhavi